2018
DOI: 10.1111/cbdd.13164
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and antiprotozoal evaluation of new 2,9‐bis[(substituted‐aminomethyl)phenyl]‐1,10‐phenanthroline derivatives

Abstract: A series of new 2,9-bis[(substituted-aminomethyl)phenyl]-1,10-phenanthroline derivatives was synthesized, and the compounds were screened in vitro against three protozoan parasites (Plasmodium falciparum, Leishmania donovani, and Trypanosoma brucei brucei). Biological results showed antiparasitic activity with IC values in the μm range. The in vitro cytotoxicity of these molecules was assessed by incubation with human HepG2 cells; for some derivatives, cytotoxicity was observed at significantly higher concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…The 3D structural determination of disubstituted indole 2 was established by X-ray crystallography (Figure 1) [21] and confirmed the structure in the solid state as anticipated on the basis of NMR data [19,20]. Condensation of 3-dimethylaminopropylamine with the aldehyde 2 led to the unstable imine 3, which was immediately reduced into the 1H-3-{4-[(3-dimethylaminopropyl)aminomethyl] phenyl}-2-phenylindole (4) using sodium borohydride as a reductive agent in refluxing methanol as previously described by our team [16,17]. The structure of this new synthesized derivative 4 was then confirmed by FTIR, 1 H/ 13 C-NMR and ESI-MS analyses (see Supplementary Materials).…”
Section: H-3-{4-[(3-ddimethylaminopropyl)aminomethyl]phenyl}-2-phenysupporting
confidence: 67%
See 1 more Smart Citation
“…The 3D structural determination of disubstituted indole 2 was established by X-ray crystallography (Figure 1) [21] and confirmed the structure in the solid state as anticipated on the basis of NMR data [19,20]. Condensation of 3-dimethylaminopropylamine with the aldehyde 2 led to the unstable imine 3, which was immediately reduced into the 1H-3-{4-[(3-dimethylaminopropyl)aminomethyl] phenyl}-2-phenylindole (4) using sodium borohydride as a reductive agent in refluxing methanol as previously described by our team [16,17]. The structure of this new synthesized derivative 4 was then confirmed by FTIR, 1 H/ 13 C-NMR and ESI-MS analyses (see Supplementary Materials).…”
Section: H-3-{4-[(3-ddimethylaminopropyl)aminomethyl]phenyl}-2-phenysupporting
confidence: 67%
“…In this last field, the indole compounds are considered as attractive candidates for antiprotozoal therapy [11][12][13][14]. In the course of our work devoted to discovering new original heterocyclic candidates for use in antiparasitic chemotherapy [15][16][17], and as an extension of our work on the development of new antimalarial indole heterocyclic drugs, we have identified 1H-3-{4-[(3-dimethylaminopropyl)aminomethyl]phenyl}-2-phenylindole and found that it is endowed with interesting activity against three protozoan parasites. Thus, we report herein on the synthesis and structural identification of this new indole scaffold, which was then screened in vitro against three protozoan parasites (Plasmodium falciparum, Leishmania donovani and Trypanosoma brucei brucei).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of the test compounds were assessed using the viability marker Alamar Blue assay described by Räz et al . After a 69 h incubation period at 37 °C, Alamar Blue (10 μL, Fisher, France) was added to each well, and the plates were incubated for 5 h . The plates were read using a PerkinElmer (Germany) ENSPIRE microplate reader using an excitation wavelength of 530 nm and an emission wavelength of 590 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Besides the quinoline‐quinoline hybrids mentioned above, some atypical quinoline dimers also possessed considerable activity against drug‐resistant P falciparum strains . Among them, dimer 34 with IC 50 of 71 and 70 nM against CQR W2 and MQ‐resistant 3D7 strains, was no inferior to MQ (IC 50 : 32 and 80 nM against CQR W2 and MQ‐resistant 3D7 strains, respectively) and CQ (IC 50 : 200 and 80 nM, respectively) …”
Section: Quinoline Hybridized With Novel Antimalarial Pharmacophores mentioning
confidence: 99%